Linguistic Marking of Interactionality of Stance in the English Blog Discourse - Shkamarda, Oksana (My University, 2019)
The present article approaches the notion of stance as an interactive and dynamic discursive phenomenon that is constructed in the process of communication through a sequence of contributions by stance-takers. The linguistic resources (lexical, grammatical and stylistic) which the speakers have at their disposal for articulating their stances have been examined and classified according to their social and pragmatic potential. The material of the research is based on online written messages taken from popular American blogs.
Keywords: stance; stancetaking; blog; discourse